A construção do sucesso na Revista Veja - Barros, Eduardo Paes de (2010)
This research intends to examine the discursive construction ways of figures of professional success in news coverage of the Brazilian weekly magazine Veja between 1968 and 2007. Those figures are individuals and companies of solid success highlighted by the announcer because of competence, high position in acting area, steady financial condition and so on. Using discourse analysis, this study aims to analyze how Veja establishes themes and figures of success, outlining, through the magazine speaker perspective, the communication contract established between the magazine and readers. From the narrative point of view, this work investigates which are the subjects and their valuable goods and how specificities are build (how to become a figure of success, how to reach that stage, what it means to be such a figure, etc.), and trace the passionate way of the characters of the narrative, linking such analysis to the figurative and thematic construction, to finally understand the reason for the prominence of the character and the kind of success made visible by the media, from the examination of the simulacra of success actually built by the reports